Redescription of Notarius grandicassis and Notarius parmocassis (Siluriformes; Ariidae), with insights into morphological plasticity and evidence of incipient speciation - Marceniuk, Alexandre P.; Siccha-Ramirez, Raquel [UNESP]; Barthem, Ronaldo Borges; Wosiacki, Wolmar Benjamin (Taylor & Francis, 2017)
The Thomas sea catfish is characterized by a highly variable parietosupraoccipital process, which has been recognized as intraspecific variation or phenotypic plasticity. On the basis of this variation, three nominal species have been described, with two of them currently considered to be junior synonyms. Here, the Notarius grandicassis species complex is reviewed, considering the geographic variation of its morphological traits. Notarius grandicassis from north-eastern South America, and Notarius parmocassis, from eastern and southern Brazil, are redescribed as distinct evolutionary units, even though they are not differentiated by partial sequences of the mitochondrial genes CytB and ATPase 8/6. This condition is interpreted as a consequence of the recent evolutionary history of these species, which are found in distinct geographic areas with different environmental conditions.
Keywords: Atlantic South America; incipient speciation; morphological plasticity; Notarius grandicassis; Notarius parmocassis